2013
DOI: 10.1021/jp404799d
|View full text |Cite
|
Sign up to set email alerts
|

Structure of PtnNi Nanoparticles Electrocatalysts Investigated by X-ray Absorption Spectroscopy

Abstract: Carbon supported Pt−Ni nanoparticles (NPs) electrocatalysts with nominal Pt/Ni atomic ratios of 3:1, 2:1, and 1:1, denoted as Pt 3 Ni/C, Pt 2 Ni/C, and Pt 1 Ni/C, respectively, were obtained by a modified polyol process. The structure of Pt n Ni/C (n = 3, 2, 1) electrocatalysts was studied by using an X-ray absorption spectroscopy technique combined with X-ray diffraction and transmission electron microscopy. Significantly, the NPs of Pt 3 Ni/C in air are demonstrated to have a quasi core−shell structure consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In general, the shapes of the Ni K-edge for the Ni 97 Bi 3 and Ni 55 Bi 45 aerogels are similar to the Ni foil, and the whiteline intensity at approximately 8351 eV is much weaker than the reported NiO. [14] These results,i nc ombination with the XPS results,indicate that the Ni in the Ni 97 Bi 3 and Ni 55 Bi 45 aerogels is statistically metallic,but on the surface it is mainly in an oxidized state.…”
Section: Forschungsartikelmentioning
confidence: 71%
“…In general, the shapes of the Ni K-edge for the Ni 97 Bi 3 and Ni 55 Bi 45 aerogels are similar to the Ni foil, and the whiteline intensity at approximately 8351 eV is much weaker than the reported NiO. [14] These results,i nc ombination with the XPS results,indicate that the Ni in the Ni 97 Bi 3 and Ni 55 Bi 45 aerogels is statistically metallic,but on the surface it is mainly in an oxidized state.…”
Section: Forschungsartikelmentioning
confidence: 71%
“…Nevertheless, due to the weak bonding with H and C, Ni surface segregation is not remarkable in a reducing atmosphere (such as H 2 or CO) . This was also confirmed by experiments . For example, Rentao et al reported reversible structural changes of Pt–Ni NPs (5∼20 nm) in alternating H 2 and O 2 environments .…”
Section: Inducing Surface Segregationmentioning
confidence: 73%
“…Further experimental work has focused on the preparation of small PtNi nanoparticles (NPs) ≤ 5 nm, with varying Pt-loading. These NPs have well-controlled octahedral geometries (FCC-type atomic arrangements) displaying extensive (111) facets, aiming for similar catalytic properties as the extended surface [12][13][14][15][16][17][18][19][20][21]. Thus, the maximisation of large surface areas offered by bimetallic NPs makes them ideal as catalysts for novel fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%